INNOVATION IN THE FIELD OF ELECTRONIC COMMERCE - A. Khochuev (Вестник Северо-Кавказского федерального университета, 2022)
The article is aimed at the comparative analysis of the main characteristics of trading platforms, as a type of innovation in electronic commerce, and identifying their pros and cons. The stated goal achieving involves solving two problems. Firstly, trading platforms' various types have been investigated. Secondly, the trading platforms' comparative description is given to determine their advantages and disadvantages, which will optimize the choice in the implementation of sales transactions on the Internet. The study has shown that the choice of a trading platform should be entirely consistent with the strategic goals and objectives of the enterprise. Based on the above analysis of three the most popular paid platforms in the Russian business, we emphasize that each of them has inherent advantages and disadvantages. Basing on the users 'feedback, the author evaluated each of three platforms, which made it possible to define AdvantShop as the most successful choice in general terms, as it has rich functionality.